2000
DOI: 10.1090/qam/1753401
|View full text |Cite
|
Sign up to set email alerts
|

Singular perturbation approach to an elastic dry friction problem with non-monotone coefficient

Abstract: Abstract.In this paper we study a one-dimensional dynamic model of dry friction with slip velocity dependent coefficient. In many cases, this model has more than one solution. We introduce a perturbed friction condition which allows us to regain the uniqueness of the solution. We show that the perturbed problem's solutions pointwise converge to a particular solution of the initial problem when the perturbation parameter tends to zero. The singular perturbation approach provides the analysis of a criterion used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 5 publications
(5 reference statements)
1
13
0
1
Order By: Relevance
“…An interesting open problem would be to study the evolution of the bifurcations (i.e., the evolution of the corresponding eigenvalue problems) when h and ∆t tend to zero. For the moment, no evidence of dynamic bifurcations has been exhibited for the continuous dynamical friction problem except when the friction coefficient is a decreasing function of the sliding velocity (see [18] and [26] for instance).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting open problem would be to study the evolution of the bifurcations (i.e., the evolution of the corresponding eigenvalue problems) when h and ∆t tend to zero. For the moment, no evidence of dynamic bifurcations has been exhibited for the continuous dynamical friction problem except when the friction coefficient is a decreasing function of the sliding velocity (see [18] and [26] for instance).…”
Section: Discussionmentioning
confidence: 99%
“…However, following the analysis performed in Renard [26], this ill-posed problem may benefit from the well-posed property of the slider. To that end a thin rigid 'sole' is positioned on the friction surface {x = 0} of the slab (see Figure 4).…”
Section: The Surface Perturbation Modelmentioning
confidence: 99%
“…A mathematical analysis of the convergence as ε vanishes can be found in Renard [25,26]. It is shown that the unique solution v ε (t) to this Cauchy problem is close to the so-called 'maximum delay' solution v md (t) of the scalar equation (2.13)-(2.14).…”
Section: The Surface Perturbation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The first method, due to Renard [17], [18], consists in adding a small mass concentrated on the friction surface. Using stability arguments, Renard has proved the convergence of the solution for a large class of loadings in the one-dimensional case.…”
Section: Introductionmentioning
confidence: 99%